PH‐EVD: A pH‐Paper‐Based Extraction and Visual Detection System for Instrument‐Free SARS‐CoV‐2 Diagnostics. Issue 2 (7th December 2021) - Ding, Xiong; Li, Ziyue; Avery, Lori; Ballesteros, Enrique; Makol, Rohit; Liu, Changchun
Abstract : The ongoing pandemic of coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has caused millions of deaths worldwide. However, most SARS‐CoV‐2 detection methods depend on time‐consuming sample preparation and large detection instruments. Herein, a method employing nonbleeding pH paper to achieve both RNA extraction and visual isothermal amplification is proposed, enabling rapid, instrument‐free SARS‐CoV‐2 detection. By taking advantage of capillary forces, pH‐paper‐based RNA extraction can be accomplished within 1 min without need for any equipment. Further, the pH paper can mediate dye‐free visual isothermal amplification detection. In less than a 46‐min sample‐to‐answer time, pH‐paper‐based extraction and visual detection (termed pH‐EVD) can consistently detect 1200 genome equivalents per microliter of SARS‐CoV‐2 in saliva, which is comparable to TaqMan probe‐based quantitative reverse transcription PCR (RT‐qPCR). Through coupling with a chemically heated incubator called a smart cup, the instrument‐free, pH‐EVD‐based SARS‐CoV‐2 detection method on 30 nasopharyngeal swab samples and 33 contrived saliva samples is clinically validated. Thus, the pH‐EVD method provides simple, rapid, reliable, low‐cost, and instrument‐free SARS‐CoV‐2 detection and has the potential to streamline onsite COVID‐19 diagnostics. Abstract : A pH‐paper‐based extraction and visual detection (termed pH‐EVD) method is developed for instrument‐free severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) detection. Nonbleeding pH paper is used for both RNA extraction and visual isothermal amplification detection. Through coupling with a chemically powered smart cup, the pH‐EVD method provides simple, rapid, reliable, low‐cost, and instrument‐free SARS‐CoV‐2 diagnostics in clinical samples.